Comparative Analysis of Effectiveness of Intercostal Nerve Block Versus Intravenous Analgesics in Chest Trauma Victims Over First 72-Hour Time Period - Ali, Mamoon; Jahan, Shazia; Shah, Saleem Raza; Ateeq, Muhammad; Akram, Javeria (Biological and Clinical Sciences Research Journal, 2025)
Chest trauma is a common emergency in Pakistan, frequently leading to significant pain and respiratory complications. Conventional intravenous (IV) analgesics may be inadequate or cause systemic side effects. Intercostal nerve block (ICNB) offers a regional technique with potential benefits, but its comparative efficacy in local trauma settings remains under-evaluated. Objective: To compare the analgesic effectiveness of ICNB versus IV analgesics in chest trauma victims over a 72-hour period. Methods: This case-control study was conducted at Aziz Bhatti Shaheed Teaching Hospital, Gujrat from 3 February to 3 May 2025. A total of 142 patients with AAST Grade I or II chest trauma were enrolled and randomly assigned to receive either ICNB (Group A) or IV ketorolac (Group B). Pain was assessed using the Visual Analog Scale (VAS) at 12, 24, and 72 hours post-intervention. Adverse effects and the need for rescue analgesia were also recorded. Data were analyzed using SPSS v22. Independent t-tests and stratification were applied with p ≤ 0.05 considered statistically significant. Results: Group A (ICNB) showed significantly lower mean VAS scores compared to Group B (IV) at 12 hours (5.01 ± 2.40 vs. 6.16 ± 2.25, p=0.001), 24 hours (3.75 ± 1.85 vs. 5.04 ± 2.50, p=0.000), and 72 hours (2.89 ± 1.54 vs. 3.65 ± 1.89, p=0.012). ICNB was also associated with fewer adverse events (nausea/vomiting: 4.2% vs. 14.1%, p=0.042) and a lower rate of rescue analgesia (5.6% vs. 19.7%, p=0.013). Stratified analysis confirmed consistent efficacy across gender and injury grades. Conclusion: ICNB offers superior pain control, fewer side effects, and better overall outcomes compared to IV analgesics in chest trauma patients. Its adoption should be considered as part of standard pain management protocols in Pakistani trauma care settings.